2018
DOI: 10.4274/jcrpe.5506
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of MKRN3 Mutation in Patients with Familial Central Precocious Puberty

Abstract: Objective:There have been recent advances in the understanding of the etiology of idiopathic central precocious puberty (iCPP) including new genetic associations. The aim of this clinical study was to determine the frequency of MKRN3 mutation in cases of familial iCPP.Methods:Potential sequence variations in the maternally imprinted MKRN3 gene were evaluated in 19 participants from 10 families using next-generation sequencing analysis.Results: MKRN3 variation was found in only one of the 19 (5.3%) subjects. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 25 publications
0
13
0
3
Order By: Relevance
“…MKRN3 defects were described in 89 patients (76 girls and 13 boys) with CPP from 17 countries: Argentina [15], Belgium [4], Brazil [4, 5, 15, 16, 31], Bulgaria [20], Cyprus [25, 26], Denmark [28], France [7], Germany [9], Greece [6], Israel [8], Italy [7, 10, 19, 27], Japan [14], Korea [12], Spain [13], Taiwan [29], Turkey [11, 30], and United States of America [4]. Eighty-eight patients harbored mutations in the coding sequence and one exhibited a deletion in the promoter region of the gene.…”
Section: Resultsmentioning
confidence: 99%
“…MKRN3 defects were described in 89 patients (76 girls and 13 boys) with CPP from 17 countries: Argentina [15], Belgium [4], Brazil [4, 5, 15, 16, 31], Bulgaria [20], Cyprus [25, 26], Denmark [28], France [7], Germany [9], Greece [6], Israel [8], Italy [7, 10, 19, 27], Japan [14], Korea [12], Spain [13], Taiwan [29], Turkey [11, 30], and United States of America [4]. Eighty-eight patients harbored mutations in the coding sequence and one exhibited a deletion in the promoter region of the gene.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, two recent studies have revealed a negative correlation between circulating MKRN3 levels and the Tanner stages of puberty in healthy children and adolescents [27,28]. Therefore, screening is recommended, in particular for MKRN3 mutations, for all patients with familial ICPP, patients with unclear family histories [3] and patients with sporadic CPP [2]. It is also important that the younger siblings of patients with familial CPP secondary to MKRN3 mutations be screened for the same mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Despite efforts to establish the genetic mechanism underlying normal and precocious pubertal timing in humans, it remains largely unknown [2]. However, gain-of-function mutations in the KISS1 and KISSR1 (previously named GPR54) genes and loss-of-function mutations in the makorin ring finger protein 3 (MKRN3) gene were shown to lead to CPP [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In girls, CPP is most commonly deemed idiopathic, for which no identifiable cause is identified (24). However, emerging genetic causes of CPP, especially mutations in Makorin Ring Finger Protein 3 (MKRN3) are increasingly being identified in cases previously deemed idiopathic (27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50). While CPP less commonly affects boys, when it does occur, it is more likely to have an identifiable pathologic cause, such as a hypothalamic hamartoma (24).…”
Section: Central Precocious Pubertymentioning
confidence: 99%
“…Serum levels of MKRN3 have also been shown to be lower in girls with CPP compared to agematched controls and comparable to children matched for pubertal stage (76,77). It would be of interest to validate the MKRN3 assay used in patients expected to have negligible MKRN3 protein synthesis, such as those with frameshift or nonsense mutations, or patients with Prader-Willi syndrome (27,29).…”
Section: Mkrn3mentioning
confidence: 99%